Academic Writing Workshops: Impact of Attendance on Performance - Nzekwe-Excel, Chinny (Journal of Academic Writing, 2014)
The purpose of this study is to explore if academic writing workshops contribute to students’ learning and performance in assessment. Academic writing workshops provide an opportunity to discuss specific learning areas and promote student engagement. The results of an assessed essay for a group of 65 first-year Mathematics students at Aston University, UK show that academic writing workshops have an association with students’ academic performance. An Independent Samples T-test was conducted to compare the mean performance of the students based on their attendance of academic writing workshops. The analyses reveal that students who attended 2-5 academic writing workhops had a far much better performance (mean: 58.60%) in comparison to students who attended 0-1 workshop (mean: 46.37%). In addition, the analyses show a statistically significant difference in the mean performance of students who attended and of students who did not attend an academic workshop specifically relating to the assessment.